2022
DOI: 10.1515/jcim-2021-0482
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous extract of Pedalium murex D. Royen ex L. leafy stem protects against lead induced testicular toxicity in Wistar rats

Abstract: Objectives Lead exposure seriously impairs male reproductive function. The protective capacity of Pedalium murex leafy stem and fruit aqueous extracts against lead testicular toxicity is evaluated to find herbals drugs able to improve semen quality. Methods Phytochemical screening were performed according to classical methods. Twenty four male rats were divided into four groups of six rats each and received the following trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Diferent experimental models have confrmed the effectiveness of P. murex leafy stem or fruit folkloric use as aphrodisiac or male fertility booster [14][15][16]. Our prior study has also revealed the protective activity of P. murex leafy stem aqueous extract at 400 mg/kg against lead-induced testicular toxicity in Wistar rats [14]. Although phytochemicals could exhibit pharmacological efects, they could however be toxic [17].…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…Diferent experimental models have confrmed the effectiveness of P. murex leafy stem or fruit folkloric use as aphrodisiac or male fertility booster [14][15][16]. Our prior study has also revealed the protective activity of P. murex leafy stem aqueous extract at 400 mg/kg against lead-induced testicular toxicity in Wistar rats [14]. Although phytochemicals could exhibit pharmacological efects, they could however be toxic [17].…”
Section: Introductionmentioning
confidence: 85%
“…Male rats were used due to the fact that this study aims to evaluate the toxicity associated with treatment of male infertility with P. murex. Tis study follows a frst one that has assessed the potential of the aqueous extracts from P. murex leafy stem and fruit in male infertility treatment [14].…”
Section: Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations